General practitioner and obstetric service in rural Nepal: A way forward - Joshi, Arbin; Awale, Pankaj; Bohler, Eric (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aims: To review different types of obstetric services provided by the general practitioners with a back-up of para-medical staffs in a rural Nepal to analyze obstacles faced in providing qualitative care. Methods: Retrospective analysis of all deliveries conducted at Okhaldhunga Community Hospital in one year duration (December 2005 to December 2006). Results: In the study period, 123 deliveries took place with 126 births due to the result of three sets of twin. Caesarean were done in 28(22.7%) and most of them being performed as emergency basis (92.8%). Of the 95 vaginal deliveries, instrumental delivery was 7.3%. One (0.8%) underwent vaginal birth after previous caesarean section (VBAC) and the episiotomy rate was 20.3%. The perinatal mortality rate was 95.23 per 1000 births. Conclusion: Obstetric service in rural Nepal can be enhanced by incorporating general practioners. Key words: Obstetric care; general practitioners; rural setting. DOI: 10.3126/njog.v4i1.3330 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 38-41